Linum lewisii Adventitious and Hairy-Roots Cultures as Lignan Plant Factories - Roméo Arago Dougué Kentsop; Roberto Consonni; Michela Alfieri; Marina Laura; Gianluca Ottolina; Iride Mascheretti; Monica Mattana (Antioxidants, 2022)
Plants synthesize specific secondary metabolites for survival, reproduction, environmental resilience, and defense. Among them, lignans are a class of polyphenols with several bioactive properties: chemopreventive, anti-inflammatory, antiviral, and antioxidant. These compounds are often extracted from field-grown plants with very low yields. To overcome these constraints, in vitro tissue cultures provide a tool to optimize large-scale production. Moreover, the use of elicitation to increase secondary metabolite production is gaining importance. The aim of this work was to develop adventitious (ARL) and hairy roots (HRL) from Linum lewisi, a species able to synthesize arylnaphthalene lignans such as justicidin B. The ARL and HRL were obtained for the first time and characterized for their phenol content, antioxidant activity, and the production of justicidin B after treatments with several elicitors and precursor feeding. Through NMR spectroscopy, other four lignans were highlighted and identified in the roots extracts. A pilot-scale bioreactor was adopted to assess the suitability of the developed root cultures for future large-scale production. The ARL and HRL cultures showed a justicidin B production higher than other Linum species cultures described up to now (75.8 mg/L and 82.2 g/L), and the production more than doubled after elicitation with MeJA.